Implikasi Filsafat Hukum dalam Melakukan Kebijakan dalam Pembuatan dan Perancangan Kontrak Internasional - Anastasia Zefanya (Yayasan Literasi Sains Indonesia, 2022)
Countries that enter into international agreements have several tools to increase the strength and credibility of their commitments, including the ability to make the agreement a formal agreement rather than soft law, provide for mandatory dispute resolution procedures, and establish monitoring mechanisms. How does international law deal with the problems of large-scale cooperation that countries in the world are facing now and will continue to face in the future? Friedmann argues that international law is moving, and must move, from the law of international coexistence, which governs diplomacy between states, to the law of international cooperation. At the same time, international contract law theorists have not shown much interest in reaching out to legal philosophers for enlightenment. Given these issues, this article aims to examine international law as a viable field of study for philosophy of law in the context of legal pluralism and also to understand the ramifications of its development for the international order. Therefore, it is necessary to discuss international treaty arrangements from the perspective of legal philosophy. This study discusses the direction of drafting contracts whose elements must be fulfilled from a legal, philosophical point of view. One way that could be used is to adopt Dworkin's strategy and incorporate the concept of law into moral arguments, this aligns with the distinction between analytical and normative jurisprudence on domestic law and the way many moral philosophers engage with questions of moral justification. The discussion of the problem in this paper uses normative juridical research methods using a descriptive research approach.